2017
DOI: 10.1590/1413-785220172505167238
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Injuries Ocurred During a Professional Soccer Championship in 2016 in São Paulo, Brazil

Abstract: Objective:To identify the incidence of injuries, their main characteristics, and the way they were managed throughout 2016 in two major series of a professional soccer championship in São Paulo, Brazil. Methods:This prospective study used an electronic questionnaire previously developed by the Medical Committee of the Paulista Soccer Federation which was sent to the team doctors after each match. Results:Two hundred and fifty-nine injuries occurred during 361 matches, and the incidence of injury per 1000 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
3
14
0
6
Order By: Relevance
“…This investigation essentially focused on the analysis of orthopedic injuries sustained in the São Paulo State Championship of Series A1 and A2, of the 2017 season, which was compared to the 2016 season 11 . The incidence and characteristics of the injuries of the 2017 season are similar to data available in the literature 3 , 14 , though both the incidence and distribution of the injuries of the injuries dropped when compared to the previous season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation essentially focused on the analysis of orthopedic injuries sustained in the São Paulo State Championship of Series A1 and A2, of the 2017 season, which was compared to the 2016 season 11 . The incidence and characteristics of the injuries of the 2017 season are similar to data available in the literature 3 , 14 , though both the incidence and distribution of the injuries of the injuries dropped when compared to the previous season.…”
Section: Discussionmentioning
confidence: 99%
“…This is a prospective study performed by means of an electronic form previously developed by the Medical Committee of the São Paulo Football Federation (Federação Paulista de Futebol), sent to the physicians in charge of the teams of the A1 and A2 series of the São Paulo State Football Championship, after each round of the 2017 São Paulo State Football Championship. Data was compared to a prior similar study conducted during the last season, following data collection and statistical analysis 11 .…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that the sport generates more than 30 billion dollars per year worldwide and is played by more than 240 million people (2) . Since it involves running, sprinting, jumping and quick changes of direction, soccer athletes are exposed to several types of injuries to the muscles and ligaments, as well as contusions and even fractures (1,3,4) . Studies have shown that soccer has a higher injury rate than other sports, including handball, volleyball, basketball, judo, and swimming (5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…The injury rate in this sport can reach 70 per 1000 hours of exposure (3) . Recent data show that the leg is the main site of these injuries, which are mainly traumatic in origin (2,3,7,8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation